Credit Card: Changing the Buying Attitudes regarding Luxury Goods and Maintaining Quality of Living Standard - Haque, Md. Alaul; Ghose, Urmee; Ahsan, Mohammod Kamrul (Asian Accounting and Auditing Advancement, 2022)
Purpose: This paper focuses on the factors that affect the buying attitude regarding luxury goods through credit cards in Bangladesh. The research also examines the degree of influence of different factors on affluent lifestyles in society. Design/Methodology/Approach: The data were collected from different areas of the Sylhet division through a structured questionnaire. Two hundred and forty-two credit card users are taken as a sample. Findings: in this study, the most important influencing factors are Needs, Benefits, Satisfaction, and Terms and Communicating Information. This study shows that all the associated factors positively affect maintaining living standards and an affluent lifestyle in society. Research Limitations/ Implications: The study results have theoretical and practical implications. The scope of the study remains limited to the Sylhet division, and the sample size is 242 due to time and area constraints. Here, demographic factors can have a substantial impact on changing the customers buying patterns towards credit cards used to maintain quality of living standards. Originality/Value: There is no previous research on credit cards in Bangladesh that states that credit cards directly influence buying attitudes regarding luxury goods, ensure the quality of living standards, and ultimately result in an affluent lifestyle in society.